The Effectiveness of the Restorative Justice Approach in the Juvenile Criminal Justice System in West Java - Murshal Senjaya; Wilman Supondho Akbar (CV. RADJA PUBLIKA, 2025)
The increasing number of juvenile delinquency cases in Indonesia raises serious concerns regarding the effectiveness of conventional punitive approaches in addressing crimes committed by children. In many cases, formal criminal proceedings tend to stigmatize children and hinder their social reintegration. To address this issue, Indonesia has adopted a restorative justice approach through diversion mechanisms regulated under Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. However, the practical effectiveness of this approach in resolving juvenile criminal cases remains a subject of debate. Therefore, this study aims to examine the effectiveness of the restorative justice approach in the juvenile criminal justice system in West Java. The research addresses the following questions: how is restorative justice implemented in juvenile criminal cases, and what factors influence its effectiveness in resolving conflicts involving children in conflict with the law? This study employs a qualitative research design using a normative juridical and socio-legal approach. Data were collected through document analysis of legal regulations and case records, as well as interviews with law enforcement officials, social workers, and community mediators involved in diversion processes. The findings indicate that restorative justice mechanisms, particularly diversion, have contributed significantly to resolving juvenile cases outside formal court proceedings. The approach facilitates dialogue between victims and offenders, promotes reconciliation, and prevents the stigmatization of children through imprisonment. However, the effectiveness of restorative justice is influenced by several factors, including institutional commitment, community participation, and the capacity of mediators in facilitating dialogue. Academically, this research contributes to the development of restorative justice scholarship by integrating normative legal analysis with empirical insights from juvenile justice practices in West Java, thereby offering a more comprehensive understanding of how restorative justice can strengthen child-centered justice systems in Indonesia.